(1‐Butyl‐3‐methylimidazolium Hexafluorophosphate) Based Sensor for Quantification of Eugenol Antioxidant. Issue 10 (6th October 2016) - Verma, Alka; Jain, Rajeev
Abstract: A simple, ultrasensitive and convenient electrochemical method has been developed for quantification of antioxidant eugenol, at multi‐walled carbon nanotube (MWCNT) ionic liquid (1‐Butyl 3‐methylimidazolium hexafluorophosphate) glassy carbon based sensor. The electrochemical behavior of eugenol at the sensor was studied using square wave voltammetry as a function of concentration of eugenol. The voltammetric studies of eugenol at MWCNT‐IL‐Gel/GC sensor exhibited a well defined anodic peak for its oxidation in Britton‐Robinson buffer at pH 10.5.Under optimized experimental condition the square wave oxidation peak current was linear over concentration range of 250 nM L −1 to 4000 nM L −1 with limit of detection (LOD) and limit of quantification of 87.6 nM L −1 and 292.2 nM L −1 respectively. The results indicate that the electrode coated with MWCNT‐IL‐Gel possess high sensitivity towards eugenol. Developed MWCNT‐IL‐Gel/GC sensor was successfully employed for the analysis of eugenol in real samples. Abstract :